Pattern of peripheral arthritis in 15 patients with ulcerative colitis - Aref Hosseinian Amiri; Vahid Hosseini; Fatemeh Niksolat Roodposhti (Wolters Kluwer Medknow Publications, 2015)
Background: Inflammatory bowel disease (IBD) including ulcerative colitis (UC) and Crohn's disease is an immune-mediated chronic intestinal condition. The arthritis accompanying the IBDs are included in the family of spondyloarthritis. Peripheral arthritis develops in about 15-20% of IBD patients. Asymmetric oligoarthicular large joint involvements have inflammatory characteristics at these patients and occur in upper and lower extremities. Aim: The aim of the study was to analyze the pattern of joint involvement in 15 patients with UC during 2 years from January 2011 to December 2013. Subjects and Methods: This is a retrospective study of UC patients with acute and chronic arthritis during 2 years from January 2011 to December 2013 that refers to rheumatologic Clinic of Mazandaran University of Medical Sciences. Data were analyzed using the SPSS version 20. Variables analyzed include age, sex, presence of arthritis/periarthritis, the number of involved joints, kind and pattern of arthritis. Results: In these study 15 patients with UC and acute arthritis refers to BAGHBAN rheumatologic clinic. All of the patients were adults between 18 and 42-year-old with median age of 31.5 years old. Ten patients (66%) were female, and five patients (33%) were male. The media duration of UC was 3.9 years. Periarthrtis occurred in 7 (46%) patients in association with arthritis. The most commonly involved join was ankle in 11 (73%) cases. Another involved joints were knee in 5 (33%), wrist in 2 (12%), MTPs in 3 (20%), MCPs in 1 (6%) and hip in 1 (6%) of cases. In 4 (27%) patients arthritis were monoarthicular, and eight (53%) of patient's arthritis were oligoathicular in 3 (20%) cases, arthritis was polyarthicular. All of the arthritis were inflammatory. In 2 (13%) of patients, arthritis were symmetric and in 9 (60%) of cases were asymmetric. Conclusion: Inflammatory joint disease including arthritis and periarthrtis are important findings in UC. Asymmetric lower extremity large joint arthritis especially in ankles are common kind of peripheral arthritis of this disease.